Nationwide investigation on organophosphate esters and di-esters in raw grains from China: Distribution, sources, and implications for risk assessment - Minmin Hou; Yichun Wang; Hao Ding; Bona Zhang; Weihua Wang; Yali Shi; Yaqi Cai (Environment International)
Studies on dietary exposure to organophosphate esters (OPEs) and diesters (di-OPEs) are limited, especially regarding di-OPEs and their presence in raw grains, which are fundamental staples of the human diet. In this study, 18 OPEs and 8 di-OPEs were measured in 289 grain samples from 13 major grain-producing regions in China belonging to four grain types: wheat, rice, maize, and soybean. Tris(2-chloroisopropyl) phosphate (TCIPP) and tris(2-ethylhexyl) phosphate (TEHP) were the dominant OPEs, while bis(2-ethylhexyl) phosphate (BEHP) was the main di-OPE. The highest concentrations of both ∑OPEs and ∑di-OPEs were observed in soybean (median: 14.9 and 1.87 ng/g, respectively), followed by wheat (4.79 and 1.69 ng/g), maize (2.63 and 1.10 ng/g), and rice (2.37 and 0.726 ng/g). The regional distribution of OPEs and di-OPEs in maize and soybean was relatively homogeneous. In wheat, both OPEs and di-OPEs were significantly higher in Sichuan and Shandong provinces, whereas the spatial patterns of OPEs and di-OPEs in rice differed, suggesting separate sources for di-OPEs. Soil type, straw turnover, and pesticide use could significantly affect the concentrations of TEHP, tri(2-chloroethyl) phosphate (TCEP), and triethyl phosphate (TEP) in grains, respectively. Except for TEHP and tris(1,3-dichloro-2-propyl) phosphate (TDCPP), whose concentrations were similar in raw and polished rice, the other 8 OPEs in raw rice accounted for only 1.9–36 % of those in polished rice reported previously, indicating industrial processing as the main source of these OPEs in marketed grains. The estimated daily intake of OPEs and di-OPEs through grain consumption were 25.0–40.4 ng/kg bw/d and 7.55–11.7 ng/kg bw/d, respectively, primarily contributed by wheat and rice, which was higher than those through dust ingestion and drinking water, suggesting that grain is the main source of human exposure. Di-OPEs directly ingested from grains are significantly higher than those derived from the metabolism of their parent OPEs, implying that estimating OPE exposure based on internal di-OPE levels is inaccurate and warrants further research.